Alliances and Nuclear Risk: Strengthening US Extended Deterrence. Issue 1 (2nd January 2022) - Frühling, Stephan; O'Neil, Andrew
Abstract: There is a fundamental tension between the Biden administration's stated intent to strengthen US alliances while at the same time reducing the role of US nuclear weapons. The credibility of extended-deterrence commitments – which in times of great-power conflict lie at the heart of US alliances – hinges on US allies and adversaries believing that Washington would resort to nuclear weapons to defend the core interests of its allies. A no-first-use or sole-purpose declaration would undermine deterrence and alliances by qualifying US security guarantees. The Biden administration and US allies should focus on coupling allied security to the threat of US nuclear use, to risks of inadvertent escalation for adversaries, and to the value of limited nuclear use in addressing conventional military imbalances in the Indo-Pacific. Forward-basing US nuclear forces in the region, where they are currently absent, is key to achieving all three of these aims.